Hydrodynamic optimization of a high-speed vessel by means of simulation-based design methodology - Timurlek, Hasan; Sener, Bekir (SAGE PUBLICATIONS LTD, 2022)
This study presents a simulation-based optimization procedure of a high-speed vessel. The presented procedure is applied on benchmark form Model 5365, a 1/8.25 scale model of the transom-stern, high-speed research vessel, R/V Athena. The procedure integrates parametric model generation, viscous numeric resistance analysis, and genetic algorithm evaluation. CAESES, a unique simulation-based design platform, is used to collect the process under one roof and handle the process automatically. The fully-parametric form is constructed by means of main characteristic curves, control curves, and various parameters to achieve quick-variation of hull forms. The numeric resistance analysis are performed via viscous flow solver and the calm-water total resistance force is defined as the optimization objective. The NSGA-II algorithm is used for evaluation of analysis results and regeneration of form variants, to achieve total resistance minimization. The optimization results show that the optimized hull form has lower resistance than Model 5365 form; a form variant with 2.02% total resistance reduction was obtained.
Keywords: Parametric ship design; form optimization; simulation-based design; computational fluid dynamics; R; V athena; model 5365; HULL; RESISTANCE; SHAPE; Engineering